Determinant of The Bitcoin Prices as Alternative Invesment in Indonesia - Gery Andrean (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2019)
The aims of this study to know the determinant that affect bitcoin prices and how bitcoin prices response to the shock from GDP (Gross Domestic Product), inflation, exchange rate, JCI (Jakarta Composite Index. The method that was used in this research was quantitative analysis, with data analysis tools Vector Error Correction Model (VECM). Data used in this research was secondary data taken from Bank Indonesia, Bitcoincharts, and Yahoo Finance. The results of this study showed that (1) inflation in short term and in long term has negative significant effect on bitcoin prices, exchange rate in long term has positive significant effect on bitcoin price. In short term and in the long term GDP and JCI do not have significant effect on bitcoin prices (2) The results of IRF shows bitcoin prices respond negatively shock from GDP and exchange rate, while shock from inflation and JCI responded posifively by bitcoin prices.